Pemaksimalan pembelajaran berdiferensiasi berbasis kelompok gaya belajar siswa dalam mata pelajaran matematika - Putri, Destalia; Mubarok, Muhammad Shofi (Karoteh Utama, 2025)
This study aims to describe the implementation of differentiated learning based on students’ learning styles (visual, auditory, and kinesthetic) in improving engagement and mathematics learning outcomes among fifth-grade students at SD Negeri Paguyangan 02. A descriptive qualitative approach was employed, using observation, interviews, and documentation for data collection. The results reveal that systematic implementation of differentiated learning significantly enhanced student engagement. The activity indicator achievement increased from 37.5% to over 80% after instruction was adjusted to match students’ learning styles. Furthermore, the average mathematics score rose from 50.71 to 85.64, with 89.7% of students achieving scores ≥80. The kinesthetic group demonstrated the highest improvement, followed by visual and auditory learners. These findings indicate that differentiated learning based on learning styles is effective in fostering active, adaptive, and student-centered instruction.